2020
DOI: 10.2147/imcrj.s274284
|View full text |Cite
|
Sign up to set email alerts
|

<p>COVID-19 Lockdown and Eye Injury: A Case Series from Jordan</p>

Abstract: Novel coronavirus or COVID-19 is a viral illness that can cause severe respiratory symptoms. It spreads between people through direct, indirect (through contaminated objects or surfaces), or close contact with infected people via mouth and nose secretions. COVID-19 has caused a worldwide pandemic that necessitated many countries to perform a national lockdown. In Jordan, a complete lockdown was imposed by the government on March 17th, 2020 and continued for more than two months. The lockdown included every sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Striking prevalence of ocular/orbital injuries after complete lockdown in the Middle East and South Asia countries may relate to household violence due to emotional stress during the quarantine and/or culture in this world region (Level of Evidence 4) [ 58 , 59 ]. Guidelines for ocular/orbital trauma surgery related to COVID-19 were proposed by Natarajan et al [ 59 ] and Wong et al [ 60 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Striking prevalence of ocular/orbital injuries after complete lockdown in the Middle East and South Asia countries may relate to household violence due to emotional stress during the quarantine and/or culture in this world region (Level of Evidence 4) [ 58 , 59 ]. Guidelines for ocular/orbital trauma surgery related to COVID-19 were proposed by Natarajan et al [ 59 ] and Wong et al [ 60 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“… 1 , 2 Reported ocular complications of the viral infection have varied from common but simple ones as ocular surface inflammation, 3 to less common but serious ones as retinal vascular occlusion, 4 optic neuritis, and ocular cranial nerve palsies. 5 Adverse ocular sequelae of the pandemic have also been linked to treatment protocols, 6 positioning during intensive care unit stay, 7 lockdown restrictions, 8 and immunization. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported 2 and 11 cases with ocular trauma due to resistance band–related exercises carried out at home,31,32 respectively. Bapaye et al33 described 2 cases of pediatric ocular trauma caused by bow and arrow at home due to imitation of TV dramas, and Alqudah et al21 reported 4 cases of open globe injury that occurred at home.…”
Section: Resultsmentioning
confidence: 99%
“…1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] There were 31 studies in English and 1 in Chinese.…”
Section: Literature Search Resultsmentioning
confidence: 99%